Resistive Ballooning Modes and the Second Region of Stability - Sykes, A.; Bishop, Christopher; Hastie, R. J. (Plasma Physics, 1987)
Resistive ballooning modes are unstable in the first region of ideal ballooning stability. We show that in contrast the second region is largely stable to resistive ballooning modes.